Ex-Post Territorial Impact Assessment of the European Union Funds Used in the 2014-2020 Programme Period - Kocziszky, György; Bánné Gál, Boglárka (Észak-magyarországi Stratégiai Füzetek, 2024)
Since its accession to the European Union (2004), Hungary has been allocated a considerable amount of EU funds intended to promote regional development and convergence. The first part of this study reviews the literature dealing with the use of EU funds. Then a developed model of ex-post impact assessments is presented. The validity of the model is examined based on the use of the cohesion resources in the 2014-2020 planning period in Mezőkövesd District, Borsod-Abaúj-Zemplén County, Hungary. The results are presented in a spider-web diagram and quantified with the help of an aggregate index.